2018
DOI: 10.1021/acs.jafc.8b04104
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Tumor Metabolism with Plant-Derived Natural Products: Emerging Trends in Cancer Therapy

Abstract: Recognition of neoplastic metabolic reprogramming as one of cancer's hallmarks has paved the way for developing novel metabolism-targeted therapeutic approaches. The use of plant-derived natural bioactive compounds for this endeavor is especially promising, due to their diverse structures and multiple targets. Hence, over the past decade, a growing number of studies have assessed the impact of phytochemicals on tumor cell metabolism, aiming at improving current knowledge on their mechanisms of action and, at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(59 citation statements)
references
References 190 publications
2
57
0
Order By: Relevance
“…While many biological and physicochemical factors have been identified in cancer development, there is an increasing interest in the role of inflammation and involvement of stromal component of the tumour microenvironment [3]. The challenge of treating breast cancer resides not only in the identification of active compounds capable of targeting the cancer, but mainly in identifying potent therapies with low side effects [4]. In this perspective, natural compounds like coumarins have gained significant interest in the recent years for their numerous pharmacological activities including chemopreventive and antiproliferative properties against various cancer types [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While many biological and physicochemical factors have been identified in cancer development, there is an increasing interest in the role of inflammation and involvement of stromal component of the tumour microenvironment [3]. The challenge of treating breast cancer resides not only in the identification of active compounds capable of targeting the cancer, but mainly in identifying potent therapies with low side effects [4]. In this perspective, natural compounds like coumarins have gained significant interest in the recent years for their numerous pharmacological activities including chemopreventive and antiproliferative properties against various cancer types [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Coumarins are heterocyclic organic compounds that are widely distributed in nature [4,9]. Coumarin derivatives have gained high scientific interest as promising drug candidates since they possess multiple pharmacological properties [10][11][12][13], such as antioxidant [14][15][16], antibacterial [17,18], antimicrobial [18], antiviral [13], hepatoprotective [19] and anti-inflammatory effects [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Natural products have been widely used for the treatment of various cancers, cardiovascular diseases and renal diseases for many years [18][19][20]. It was reported that 46% of drugs approved by food and drug administration are derived from natural small molecules from 1981 to 2014 [21].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that 46% of drugs approved by food and drug administration are derived from natural small molecules from 1981 to 2014 [21]. Reportedly, many natural small molecules from natural products have many effective pharmacological activities, including anti-cancer, anti-bacterial, anti-fibrotic and anti-oxidant activities, which fueling considerable enthusiam for natural products as a source of pharmaceutical exploitation [19,[22][23][24][25][26][27][28][29]. As thus, we posited that targeting the Wnt/β-catenin pathway with natural small molecules may 2.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the favorable pharmacological and toxicological profiles of these natural substances and their ability to modulate different targets and signaling pathways involved in cancer allow their clinical use either alone or in combined treatment with chemotherapeutic agents. 1 Among these natural compounds, plumbagin (5-hydroxy-2-methyl-1,4-naphthoquinone) is a naphthoquinone extracted from the roots of Plumbago zeylanica L., a medicinal plant also known as "Chitrak" in Ayurveda medicine. [2][3][4] Plumbago zeylanica is a large perennial shrub belonging to the Plumbaginaceae family that can be found in a wild state throughout India.…”
mentioning
confidence: 99%